AZD0530 sensitizes drug‐resistant ALK‐positive lung cancer cells by inhibiting SRC signaling. Issue 4 (10th March 2017) - Zhao, Yi; Yang, Yi; Xu, Yunhua; Lu, Shun; Jian, Hong
Abstract : Most tumors develop resistance to targeted cancer drugs, even though these drugs have produced substantial clinical responses. Here we established anaplastic lymphoma kinase (ALK)‐positive drug‐resistant lung cancer cell lines, which are resistant to ceritinib (LDK378). We found that ceritinib treatment resulted in robust upregulation of SRC activity, as measured by the phosphorylation of the SRC substrate paxillin. Knockdown of SRC alone with siRNA effectively sensitized ceritinib resistance in ALK‐positive cells. Furthermore, SRC inhibition by AZD0530 was effective in ALK‐resistant cancer cells. Thus, ALK inhibition by ceritinib may lead to upregulation of SRC signaling, and AZD0530 could serve as a potential drug in the clinic to treat ALK‐resistant lung cancer patients. Abstract : Treatment of ALK‐positive cancer cell lines with ceritinib causes death of most of the cells, but surviving cells acquire resistance to ceritinib by activating the SRC signaling pathway. SRC inhibition by AZD0530 could inhibit cell proliferation in ceritinib‐resistant cells. Thus, AZD0530 could be a potential effective drug in clinic to treat ceritinib‐resistant ALK + lung cancer patients.